P-108 MARJOLIN'S ULCER AS A COMPLICATION OF UNRESOLVED OPEN ABDOMEN. (13th October 2022) - Olona, C; Casanova, R; Vadillo, J; Julià, E; Varona, A; Ferreres, J; Rodrigo, M; Jorba, R
Abstract: Introduction: Marjolin's ulcer (MU) is a rare cutaneous tumour, commonly associated with chronic wounds with difficult healing. We present a case of UM diagnosed on a persistent unresolved open abdominal closure wound. Materials and Methods: 80-year-old male with a history of ruptured infrarenal aortic aneurysm (2010) that required aorto-unifemoral repair. Postoperative period requiring decompressive laparotomy for abdominal compartment syndrome and treated with negative pressure therapy, and impossibility of definitive abdominal closure due to abdominal muscle retraction. Loss of outpatient follow-up for 10 years. Consultation for worsening of the surgical wound with abdominal pain. Examination revealed abdominal incisional hernia M2–4W3 and large abdominal ulcer. Biopsies positive results for squamous cell carcinoma with infiltrative pattern. A computed tomography describes an abdominal wall mass of 14×6×11cm and space-occupying lesion in the left hepatic lobe. Liver biopsy showed a moderately differentiated hepatocarcinoma. Surgical management consist in intramuscular injection of botulinum toxin and en bloc resection of granulation and ulcerated tissue and ileal loop attached to the lesion. Wall reconstruction with anterior separation of components and supraponeurotic mesh. Conclusions: Marjolin's ulcer is associated with squamous cell carcinoma with a high rate of metastasis and mortality. This tumour is considered infrequent, of long-term duration and associated with developing societies. In our environment, this neoplasia can develop in patients with open abdomen treated partially or with closure by second intention, so we consider it necessary to have a high index of diagnostic suspicion in these cases and to perform biopsies for its detection.